Development of a Chronic Canine Ovariohysterectomy Model to Evaluate Vaginal Cuff Healing Using Two Closure Systems. (April 2022) - Wiseman, David; Hanzlik, Josa A.; Richardson, James A.; Shelton, John M.; Evers, Bret M.; Diamond, Michael P.; Brown, Ryan; Mazzucco, Dan C.
Background and Purpose. This study established a suitable animal model of ovariohysterectomy; characterized the course and pattern of vaginal healing after ovariohysterectomy; and compared healing obtained after closure of the vaginal cuff with a novel cuff-closure device (Zip-stitch® clips) and VICRYL ® sutures. Research Design and Study Sample. This prospective, randomized, controlled, blinded animal study was conducted in 27 mongrel hounds according to an IACUC-approved protocol. Each animal underwent ovariohysterectomy followed by vaginal cuff closure with Zip-stitch or VICRYL. At two or six weeks, animals were sacrificed for gross and histological analysis. Data Collection. The primary endpoint was the difference in the fraction of vaginal cuff healed six weeks after application of the closure device. Secondary endpoints included histopathologic cellular and tissue responses, including inflammation, necrosis, infection, and vascular and muscle changes. Results. In the test group, there were two distinct locations where fibrotic or granular tissue fusion between the anterior and posterior vaginal walls was observed: in tissue "captured" by a clip or in tissue around the clip. The fraction of the vaginal cuff healed was similar in animals treated with Zip-stitch clips and those treated with sutures at six weeks (68±10% vs 67±18%; P=.148, test for non-inferiority) after surgery. The test article performed similarly or better than the control article in terms of the intensity or extent of the secondary endpoints. Conclusions. Subject to further confirmation, this study supports Zip-stitch clips as a method to maintain immediate post-operative approximation of the vaginal cuff leading to healing but did not achieve statistical significance in its primary endpoint.